Mitogen-Activated Protein Kinase Cascades in Plant Hormone Signaling - Jagodzik, Przemysław; Tajdel-Zielinska, Małgorzata; Ciesla, Agata; Marczak, Małgorzata; Ludwikow, Agnieszka (Frontiers in Plant Science, 2018)
Mitogen-activated protein kinase (MAPK) modules play key roles in the transduction of environmental and developmental signals through phosphorylation of downstream signaling targets, including other kinases, enzymes, cytoskeletal proteins or transcription factors, in all eukaryotic cells. A typical MAPK cascade consists of at least three sequentially acting serine/threonine kinases, a MAP kinase kinase kinase (MAPKKK), a MAP kinase kinase (MAPKK) and finally, the MAP kinase (MAPK) itself, with each phosphorylating, and hence activating, the next kinase in the cascade. Recent advances in our understanding of hormone signaling pathways have led to the discovery of new regulatory systems. In particular, this research has revealed the emerging role of crosstalk between the protein components of various of signaling pathways and the involvement of this crosstalk in multiple cellular processes. Here we provide an overview of current models and mechanisms of hormone signaling with a special emphasis on the role of MAPKs in cell signaling networks.